2010
DOI: 10.1186/1475-9276-9-16
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in utilization of maternal health interventions in Namibia: implications for progress towards MDG 5 targets

Abstract: BackgroundInequities in the utilization of maternal health services impede progress towards the MDG 5 target of reducing the maternal mortality ratio by three quarters, between 1990 and 2015. In Namibia, despite increasing investments in the health sector, the maternal mortality ratio has increased from 271 per 100,000 live births in the period 1991-2000 to 449 per 100,000 live births in 1998-2007. Monitoring equity in the use of maternal health services is important to target scarce resources to those with mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
85
4
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 20 publications
18
85
4
1
Order By: Relevance
“…This is in line with studies in developing countries that have examined how gendered norms and values continue to influence access and utilization of sexual and reproductive health services in patriarchal settings [24,25]. Prior studies in Namibia have documented wide disparities in health care utilization that are rooted in income and health access inequalities, including in the areas of immunizations and maternal services [26,27]. These studies reveal that over 80% of Namibians rely on poor-quality health services provided by the public health system, with only a few public sector employees covered under health insurance or with private health insurance coverage [28] The positive association between birth-parity and cervical cancer testing is worth noting.…”
Section: Discussionsupporting
confidence: 54%
“…This is in line with studies in developing countries that have examined how gendered norms and values continue to influence access and utilization of sexual and reproductive health services in patriarchal settings [24,25]. Prior studies in Namibia have documented wide disparities in health care utilization that are rooted in income and health access inequalities, including in the areas of immunizations and maternal services [26,27]. These studies reveal that over 80% of Namibians rely on poor-quality health services provided by the public health system, with only a few public sector employees covered under health insurance or with private health insurance coverage [28] The positive association between birth-parity and cervical cancer testing is worth noting.…”
Section: Discussionsupporting
confidence: 54%
“…Yet, there were pro rich inequities in utilization of treatment. Similarly in Namibia, the rich are also 30% more likely to use formal maternal services than the poor (Zere et al, 2010). Gwatkin (2001) and Gwatkin et al (2000: 721) provide further evidence from over forty countries in Africa, Asia, and Latin America, where it was found that uptake for oral rehydration therapy was 10-20% higher for the upper classes, and immunization rates for the poor were only around half that of the rich.…”
Section: (D) Health Outcomes and Inequalities In Utilization And Benementioning
confidence: 94%
“…For this, we compare well-being indicators of women who suffered a near miss event and those who had an uncomplicated delivery. However, differences in well-being indicators may be biased by socio-economic differences that already existed between the two groups, which in this setting is more likely because our sample is hospital-based: women from wealthier households tend to go to hospital irrespective of expecting complications [26-30], while women from poorer households only go to hospital when expecting complications or when unexpected complications suddenly arise. Women with complications who were selected into our sample may, on average, be poorer than women without complications.…”
Section: Methodsmentioning
confidence: 99%